The Influence of Sales Promotion and Product Quality on Purchasing Interest of Local Fashion Brand - Andrian, Andrian; Anwar, Misbahul; Wijayaningsih, Rini (East Asian Journal of Multidisciplinary Research, 2024)
The purpose of this study was to examine the effect of sales promotion and product quality on buying interest in local fashion brand. The method used in this study is a survey method with data obtained through questionnaires distributed to 155 respondents or samples based on purposive sampling. Then an analysis of the data obtained using quantitative data analysis was carried out. Quantitative analysis includes validity and reliability tests, classical assumption test, multiple linear regression analysis, hypothesis testing through t test and f test, and analysis of the coefficient of determination (R2). The results of this study indicate that the coefficient of determination involved in the adjusted R square value is 0.617, which means that the influence of sales promotion and product quality on buying interest is 61.7% and the remaining 38.3% is influenced by other variables not examined in this study.